Self-initiated expatriates: personality traits and employer attractiveness - Monteiro, Inês Ventura Lourenço Morais (2017)
The available literature about Self-Initiated Expatriates (SIEs) is still lacking studies focusing on their personality traits and their main ambitions regarding employer branding when looking for a job abroad. The goal of this paper is to explore personality traits and understand main preferences in Employer Attractiveness factors. For this purpose, an online survey with 309 individuals from different nationalities was conducted. Results suggest differences in terms of openness to experience, as well as a new categorization for the attraction factors of employer branding, considering the impact of cultural differences in this selection especially regarding Portuguese SIE attraction preferences.